Developing Essential Financial Markets in Smaller Economies : Stylized Facts and Policy Options. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper surveys the foreign exchange markets, money and secondary government security markets, and stock exchanges in 107 smaller economy countries. The underdevelopment of these markets impedes risk transfer, monetary policy, corporate financing, and the capacity to absorb capital inflows. This study marks a first step toward formulating policies to develop essential smaller economy financial markets by documenting the stylized facts and presenting a framework for assessing the policy issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet